Olfactory Preservation in Craniofacial Resection of Tumor Invading Hemianterior Skull Base: Operative Video - Kobayashi, Kenya; Miyakita, Yasuji; Matsumoto, Fumihiko; Omura, Go; Matsumura, Satoko; Ikeda, Atsuo; Eguchi, Kohtaro; Ito, Akiko; Narita, Yoshitaka; Akazawa, Satoshi; Yoshimoto, Seiichi (Journal of Neurological Surgery Part B: Skull Base, 2021)
In traditional craniofacial resection of tumors invading the anterior skull base, the bilateral olfactory apparatus is resected. Recently, transnasal endoscopy has been used for olfactory preservation in resections of unilateral low-grade malignancies. However, for tumors that invade the orbita or for high-grade malignancies, the transnasal endoscopic skull base surgery has been controversial. This video demonstrates the surgical techniques of olfactory preservation during craniofacial resection of a high-grade malignancy invading the hemianterior skull base and orbita.We present the case of a 32-year-old woman with osteosarcoma in the right ethmoid sinus. The tumor invaded the ipsilateral cribriform plate, dura menta, and orbital periosteum; however, the nasal septum and crista galli were intact (Fig. 1A, B). Because the tumor was a high-grade malignancy and the orbita had been invaded, we performed craniofacial resection instead of endoscopic resection (Fig. C2A). We drilled into the right side of the crista galli, midline of the cribriform plate, and perpendicular plate of the ethmoid bone via craniotomy. As a result, we accessed the nasal cavity directly (Fig. 2B). To preserve the nasal septum, we detached the remaining right septal mucosa through the transfacial approach (Fig. 2C). Because of the high risk of cerebrospinal fluid leakage as a result of previous irradiation, we performed vascularized free flap reconstruction of the skull base instead of pericranial flap.Postoperative computed tomography revealed no evidence of tumor (Fig. 1C, D). The patient's sense of smell returned after 1 postoperative day, and she was discharged on the postoperative day 14.The link to the video can be found at: https://youtu.be/XzPABYwzkjs.
Keywords: olfactory preservation; craniofacial resection; hemianterior skull base; ethmoid sinus; craniotomy